1999
DOI: 10.1890/0012-9658(1999)080[1852:poicfa]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Production of Inorganic Carbon From Aquatic Macrophytes by Solar Radiation

Abstract: Solar radiation causes considerable photochemical effects on dissolved organic matter (DOM) from both fresh and marine waters. Photooxidation of DOM to dissolved inorganic carbon (DIC) has been shown to be a quantitatively significant process in the turnover of DOM. Less is known about photodegradation of particulate organic matter, e.g., plant detritus. We have evaluated direct and indirect (via photooxidation of DOM released from plant detritus) photooxidative inorganic-carbon production from detritus of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(29 citation statements)
references
References 24 publications
0
29
0
Order By: Relevance
“…Water provides the hydrogen that can act as electron donors. For example, appropriate water can stimulate the photodegradation, as reported by Anesio et al (1999). How moisture and its interactions with oxygen affect the photodegradation needs further investigations.…”
Section: Photodegradationmentioning
confidence: 92%
See 1 more Smart Citation
“…Water provides the hydrogen that can act as electron donors. For example, appropriate water can stimulate the photodegradation, as reported by Anesio et al (1999). How moisture and its interactions with oxygen affect the photodegradation needs further investigations.…”
Section: Photodegradationmentioning
confidence: 92%
“…The idea of NM-CO 2 production from terrestrial ecosystems originated from studies of litter decomposition in arid and semiarid regions at the end of 1980s, when researchers found abiotic processes rather than only biotic processes also play a significant role in litter mass loss (Montaña, Ezcurra, Carrillo, & Delhoume, 1988;Moorhead & Reynolds, 1989). Not until 1999, however, were there direct measurements of CO 2 production from photodegradation of particular organic matter (POM) from plant detritus (Anesio, Tranvik, & Gran eli, 1999). During this period, investigations into oceanic carbon cycling around 1990 to a great extent facilitated its finding.…”
Section: Discovery Of Nm-ghgsmentioning
confidence: 99%
“…The increase in DOC concentration might accelerate litter mass loss in several ways. DOC itself easily undergoes photodegradation, which has been widely observed in aquatic ecosystems (Anesio et al, 1999;Macdonald & Minor, 2013). In addition, the loss DOC due to leaching during rainfall would be increased due to the increased amount of DOC in litter under higher UV radiation (Gallo et al, 2009).…”
Section: Doc Concentrationmentioning
confidence: 99%
“…Little is known about the contribution of photodegradation to CO 2 production in terrestrial systems. Only one previous study, using leaf litter of three aquatic macrophyte species, has demonstrated that CO 2 can be produced via photodegradation of dried leaves in the air [Anesio et al, 1999a]. However, the factors controlling rates of photochemical CO 2 production remain unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, one would expect that litter with a higher initial lignin concentration may produce photochemically derived CO 2 at a higher rate. Other evidence suggests that leaf surface area may be a more important driver than litter chemistry [Anesio et al, 1999a;Gallo, 2006], as photochemical reactions can only occur on surfaces exposed to radiation. To date, there is insufficient information to determine whether litter chemistry, surface area, or both are important in driving photochemical CO 2 production.…”
Section: Introductionmentioning
confidence: 99%